Nineteenth-century America through the Eyes of John Gennadius - Christopoulos, Marianna D. (The Historical Review/La Revue Historique, 2015)
The aim of this article is to unfold and analyze the view of America held by John Gennadius [Ioannis Gennadios], one of the most important diplomats of nineteenthcentury Greece. Having spent most of his life in England as a member of the Greek legation, which he served for more than 20 years, Gennadius was influenced by the ongoing British discussion of the “American miracle”. His perception was, however, fostered during two visits to America, a professional one (1888) and a private one (1893-1894). He was involved in American political life as the official negotiator of the Greek government, but also enjoyed the culture, witnessed the wealth and the galloping development and made many acquaintances. All of this made an impression on him. He commented on the importance of British influence on American civilization, acknowledged the material and intellectual progress of its people and foresaw the potential of its thriving economy in world politics.